A case of acute embolic stroke resulting from endocarditis and aortic aneurysm concurrent with aortic dissection in a healthy young patient: a case report - Sahar Hojat Ansari; Mehrdad Salehi; Niloufar Akbari Parsa; Aboozar Fakhr Mousavi (Journal of Medical Case Reports)
Abstract Background Acute ischemic stroke caused by septic embolism due to endocarditis is a rare but serious condition, especially in young patients without known risk factors. Case Summary We present the case of a 31-year-old healthy Gilaks man from Iran with a complaint of fever and chills. Initial assessments identified an acute embolic stroke. Additional tests such as brain magnetic resonance imaging and transesophageal echocardiography revealed endocarditis with an aortic aneurysm and dissection. Successful Bentall repair of the aortic root was performed at Imam Khomeini Hospital in Tehran. He left the hospital in good health. Follow-up outpatient visits in our neurology clinic confirmed a stable recovery. Conclusion Clinicians should consider endocarditis and aortic dissection as potential causes of embolic stroke, even in young, healthy patients. Early diagnosis and management are necessary to improve outcomes.